INVESTIGATING THE ANTIMICROBIAL POTENTIAL OF INDIGENOUS ENDOPHYTIC FUNGI FROM MEDICINAL PLANTS IN ANAMBRA STATE, NIGERIA, FOR NOVEL ANTIBIOTIC DEVELOPMENT (International Journal of Functional Research in Science and Engineering (IJFRSE), 2026)
This paper assesses the antimicrobial properties of endophytic fungi growing on selected medicinal plants within the State of Anambra, Nigeria, with a view of developing new antibiotics against the backdrop of the increasing antimicrobial resistance. The main aim was to isolate and identify endophytic fungi of Ocimum gratissimum, Vernonia amygdalina, and Azadirachta indica, screen, the bioactive compounds and determine the activity against pathogens, Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa, characterize promising compounds, and evaluate scalability to produce antibiotics. The research was done in the rural and peri-urban regions of Awka, Onitsha and Nnewi and involved gathering 300 plants samples (100 each species) in 15 sites, which were then isolated through surface sterilization and growth on potato dextrose agar. Id was done through morphology and molecular techniques such as ITS sequencing where 62 distinct isolates were obtained. Agar well diffusion screening showed that 18 isolates have significant activity with minimum inhibitory concentration of 0. 25 to 8 mg/mL. Key compounds were also characterized by high-performance liquid chromatography and novel polyketides and alkaloids with broad-spectrum activity were identified. ANOVA statistical analysis was used to establish that the difference in activity was significant among the isolates (p < 0.05). The research indicates endophytic fungi as unexploited resources to address antibiotic resistance, which has added value to microbiology by offering empirical evidence on the biodiversity of Nigerian areas and presented a guideline on regional adaptations. This article highlights the value of indigenous resources in innovation in health, and possible therapeutic innovations made locally. Limitations: The testing is only due to laboratory scale implying that in vivo testing should be carried out in the future. In general, this paper suggests a scalable endophyte-based drug discovery model in a developing environment.